Incidence and Risk Factors for Early Acute Kidney Injury in Nonsurgical Patients: A Cohort Study - Javier Enrique Cely; Elkin José Mendoza; Carlos Roberto Olivares; Oscar Julián Sepúlveda; Juan Sebastián Acosta; Rafael Andrés Barón; Juan José Diaztagle (International Journal of Nephrology)
Introduction. Detecting acute kidney injury (AKI) in the first days of hospitalization could prevent potentially fatal complications. However, epidemiological data are scarce, especially on nonsurgical patients. Objectives. To determine the incidence and risk factors associated with AKI within five days of hospitalization (EAKI). Methods. Prospective cohort of patients hospitalized in the Internal Medicine Department. Results. A total of 16% of 400 patients developed EAKI. The associated risk factors were prehospital treatment with nephrotoxic drugs (2.21 OR; 95% CI 1.12–4.36, p=0.022), chronic kidney disease (CKD) in stages 3 to 5 (3.56 OR; 95% CI 1.55–8.18, p<0.003), and venous thromboembolism (VTE) at admission (5.05 OR; 95% CI 1.59–16.0, p<0.006). The median length of hospital stay was higher among patients who developed EAKI (8 [IQR 5–14] versus 6 [IQR 4–10], p=0.008) and was associated with an increased requirement for dialysis (4.87 OR 95% CI 2.54 to 8.97, p<0.001) and in-hospital death (3.45 OR; 95% CI 2.18 to 5.48, p<0.001). Conclusions. The incidence of EAKI in nonsurgical patients is similar to the worldwide incidence of AKI. The risk factors included CKD from stage 3 onwards, prehospital treatment with nephrotoxic drugs, and VTE at admission. EAKI is associated with prolonged hospital stay, increased mortality rate, and dialysis requirement.